Differences Of Anaemia Status, Nutritional Status And Nutritional Intake Adolescent Girl In Urban And Rural Areas - Miratul Haya; Elvi Destariyani (Politeknik Kesehatan Kemenkes Jakarta II, 2020)
Adolescence is a transition from childhood to adulthood which is marked by a number of biological, cognitive, and emotional changes. Adolescent nutritional status is very influential on brain growth needed for cognitive and intellectual processes. The emergence of adolescent nutrition problems is basically due to the wrong eating consumption behavior. A diet that is not balanced with the body's nutritional needs will cause the body to lack iron. Persistent iron deficiency in adolescent girls can cause hemoglobin (Hb) levels in the blood to decrease and cause anemia. The objective was to analyze differences in anemia status, nutritional status and nutritional intake of adolescent girls in urban and rural areas. This type of research is cross sectional with research sites in SMAN 2 Bengkulu City and SMAN 4 Bengkulu Utara. The sample of the study was young women who met the inclusion and exclusion criteria of 130 people. Data collected was characteristic of sample data obtained through questionnaires, anemia status data obtained from Hb examination using a digital hemoglobinometer, nutritional status data obtained by anthropometric index IMT / U and nutritional intake data, data were collected using the SQ-FFQ method. Data analysis using Independent t-test if the data with normal distribution and Mann Whitney U test for data with abnormal distribution. The result is, there was no difference between anemia status, nutritional status and intake of vitamin C in young women in urban and rural areas. There is a difference between protein intake and iron adolescent girls in urban and rural areas.